Historical background and basic elements of the ideal of Chinese traditional management education - M. Yu. Zakharov; A. V. Shishkova (Вестник университета)
The article is devoted to determining the specifics of the ideal of traditional management education in China in the context of the modern strategy of China’s digital breakthrough. Using historical-philosophical, comparative and hermeneutic methods, the authors refer to the works of thinkers of Old China and modern researchers on the topic of education and public administration, and identify the components of the ideal traditional management education. It is stated that the ideal of management education is historical in nature, continuously developing and consists of a traditional core, which needs to be preserved and protected, and a “floating” part that is always adjusted in the conditions of changing reality. The Chinese society is characterised by the constant presence among the components of the national idea that lies in the dream to form a perfect managerial education based on historical practice which solved the state task of training managers of various levels. The historical prerequisites for the formation of such an ideal are described and the development of the modern system of education of civil servant is shown. Three main elements of the traditional education system are emphasised: concentration of knowledge under control of the national caste of managers; cognitive duality teacher-pupil as the basis of the learning process; stimulation of public education in contrast to home schooling. It is concluded that effective managerial education is impossible without a socio-cultural basis, a kind of educational ideal which fulfills the regulatory function.